2017
DOI: 10.1039/c7nj02454a
|View full text |Cite
|
Sign up to set email alerts
|

Acridone in a biological nanocavity: detailed spectroscopic and docking analyses of probing both the tryptophan residues of bovine serum albumin

Abstract: AD initially gets hooked to Trp 212 housed in domain IIA, inducing conformational changes in the protein and paving the way for the ligand to reach Trp 134 located in domain IB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…The presence of a single isoemissive point indicates the existence of two species in the excited state, viz., free βLG and βLG bound to AD. While studying the interaction of AD with HSA, a protein with a sole Trp residue, we have observed a single isoemissive point in the TRANES, 15 implying the involvement of a single Trp in interaction with AD; however, while studying the interaction of AD with BSA, 16 a protein with two Trp residues in varied environments, we have reported that TRANES contained two isoemissive points emerging at different time intervals, which is rationalized in the light of involvement of both the Trp residues of BSA in interaction with AD. In the present case, owing to the emergence of a single isoemissive point in the TRANES, it seems that only one Trp residue of βLG directly interacts with the acridine derivative, inspite of the fact that βLG contains two Trp residues in varied environments and as inferred from the time-resolved fluorescence study, the interacting Trp residue is possibly Trp-19.…”
Section: ■ Experimental Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…The presence of a single isoemissive point indicates the existence of two species in the excited state, viz., free βLG and βLG bound to AD. While studying the interaction of AD with HSA, a protein with a sole Trp residue, we have observed a single isoemissive point in the TRANES, 15 implying the involvement of a single Trp in interaction with AD; however, while studying the interaction of AD with BSA, 16 a protein with two Trp residues in varied environments, we have reported that TRANES contained two isoemissive points emerging at different time intervals, which is rationalized in the light of involvement of both the Trp residues of BSA in interaction with AD. In the present case, owing to the emergence of a single isoemissive point in the TRANES, it seems that only one Trp residue of βLG directly interacts with the acridine derivative, inspite of the fact that βLG contains two Trp residues in varied environments and as inferred from the time-resolved fluorescence study, the interacting Trp residue is possibly Trp-19.…”
Section: ■ Experimental Methodsmentioning
confidence: 78%
“…Previously, we have reported the interactions of an acridine derivative, acridone (AD), as depicted in Figure 1, with two model with two model proteins, human serum albumin (HSA) 15 and bovine serum albumin (BSA). 16 HSA consists of a single Trp (Trp-214) residue, which is housed in a hydrophobic cavity, whereas, BSA contains two Trp residues between which Trp-212 resides in a hydrophobic pocket while Trp-134 is solvent exposed. We have observed that in case of AD−HSA interaction, AD directly interacts with Trp-214 while in case of AD−BSA interaction, AD initially gets hooked to Trp-212 inducing strong conformational changes in the protein, which finally paves its way to reach Trp-134.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Tryptophan (Trp) and tyrosine (Tyr) residues are the major fluorophores in proteins and very sensitive to their microenvironment. Therefore, Trp and Tyr residues are ideal indicators for studying protein structural changes upon ligand binding . In this study, inner filter effects were ignored because the sum of absorptions of CdCl 2 at the excitation and emission wavelength of α‐ChT caused less than 5% error .…”
Section: Resultsmentioning
confidence: 99%
“…13. This protein exhibited two clear minima near 210 (π → π* transition) and 220 nm (n → π* transition), appearing due to the interlinks of peptides in α-helix [98]. The CD data were expressed in terms of MRE (mean residue ellipticity) and then the percentage of α-helical content of BSA was calculated via combining Eqs.…”
Section: Circular Dichroism Spectroscopymentioning
confidence: 99%